Anti-Nuclear Antibody Quantitation: Calibration and Harmonization Adjustment via Population Interrogation. (5th January 2022) - Wener, Mark H; Fink, Susan L; Morishima, Chihiro; Chaudhary, Anu; Hutchinson, Kathleen
Abstract: Background: The 2019 classification criteria for systemic lupus erythematosus (SLE) includes an initial criterion requiring the presence of an antinuclear antibody (ANA), positive at a titer of at least 1:80 on HEp-2 cells, or equivalent. However, results of ANA tests performed on HEp-2 cells vary when tested in different laboratories. Calibration of ANA assays by achieving a common specificity in healthy control populations offers the possibility of achieving harmonization via population interrogation, but the expected specificity in a healthy control population is not known. Methods: The studies used to determine the use of ANAs performed by immunofluorescence microscopy on HEp-2 cells as the entry criterion for classification of SLE were reanalyzed by a meta-analysis to determine the expected frequency of positive ANAs in healthy control populations at serum dilutions of 1:40 and 1:80. Results: Our meta-analysis demonstrated that the expected specificity in a healthy control population of ANA performed using serum diluted 1:80 is 91.3% (CI 86.1–94.7%). The expected specificity of ANA performed at 1:40 serum dilution is 79.2% (CI 72.3–84.8%). Conclusion: One approach to achieving harmonization of ANA assays from different laboratories with each other and with expected performance would involve adjusting assays so that about 10% of a healthy control population has a positive ANA when tested at 1:80 dilution, and about 20% of the healthy control population has a positive ANA when tested at 1:40 dilution. This pragmatic approach to calibration and harmonization adjustment via population interrogation offers an opportunity for individual laboratories to be aligned with each other and with ANA performance expected for consistent categorization of patients with SLE.